A brief history of formation of the kalmyk collection in the oriental section of the saint petersburg university scientific library - Vladimir L. Uspensky (Монголоведение)
Introduction. The collection of manuscripts and printed books in the Oirat Сlear Script, stored at St. Petersburg State University, is of great importance for the study of the history and culture of the Oirats, especially the Kalmyks. Although the collection of books on “clear Script”, stored at St. Petersburg State University, is one of the best in the world, the history of its formation and composition has never been the subject of special research. Meanwhile, this collection was collected by outstanding orientalists of the 19th century, and although the origin of some manuscripts is obscure, this fact does not make them less valuable. Therefore, the main purpose of this article was to find out the history of the formation of the collection to give an overview of the materials contained in it. Results. This collection brought together in the 19th century by the efforts of such outstanding Russian Mongolologists as A. V. Popov, V. P. Vasiliev, K. F. Golstunsky and A. M. Pozdneev. The collection mainly contains Buddhist books. The manuscripts collected by V. P. Vasiliev belonged to the seventeenth son of the Kangxi Emperor (reigned 1661–1722) Yunli (1697–1738) and are mostly unique or very rare. In 1860, K. F. Golstunsky handed over to the university library the manuscript of the “Biography” of Zaya Pandita (Calm C 20), written in gold on dark paper, which became a “calling card” of the Kalmyk Foundation. An important place in the collection is occupied by personal archival materials of scholars G. S. Lytkin and N. A. Lebedev. G. S. Lytkin stayed in the Kalmyk Steppe in 1859–1860 and during this time collected extensive historical and ethnographic materials. N. A. Lebedev was a translator in the Asian Department of the Ministry of Foreign Affairs and translated medical writings into Kalmyk from Russian, as well as laws and educational books. Conclusions. The collection of books in Clear Script, kept at St. Petersburg State University, is a collection of the most valuable sources for studying the history of the Kalmyks and their spiritual culture. Buddhist writings make up the bulk of the collection. Russian and Kalmyk parallel texts, as well as Russian texts with Kalmyk translations of separate words and expressions, are valuable sources for studying the vocabulary of the Kalmyk language. Many texts are valuable legal documents date back to the first half of the 19th century.